Efektivitas Deep Tissue Self Massage Therapy Dan Slow Deep Breathing Terhadap Penurunan Tekanan Darah Pada Klien Dikeluarga Pedagang Pasar Tradisional - Abidin, M. Zainal; Prasetyo, Agus; Taryatmo, Taryatmo; Warijan, Warijan; Ulliya, Sarah (Care : Jurnal Ilmiah Ilmu Kesehatan, 2022)
The prevalence of hypertension in traditional market traders is increasing, due to stress, work pressure, physical, and mental fatigue, and the burden of life. Hypertension can be prevented and controlled with non-pharmacological therapy by regulating lifestyle and relaxation. The purpose of this study was to identify the effectiveness of Deep Tissue Self Massage Therapy and Slow Deep Breathing in reducing blood pressure in hypertensive clients in families who work as traditional market traders. Quasi-experimental research design with two groups pretest-posttest used. Paired sample t-test was used in both groups before and after the intervention. Samples were collected using a proportional stratified random sampling technique with 100 respondents divided into 50 participants in each group. The results showed there was a decrease in systolic and diastolic blood pressure after the intervention of Deep Tissue Self Massage Therapy (tb = 7,997; pb = 0,004); (ta = 6.018; pa = 0.000), and there was a decrease in systolic and diastolic blood pressure after the Slow Deep Breathing intervention (tb = 7.311; pb = 0.000); (ta = 6.032; pa = 0.000). In conclusion, Deep Tissue Self Massage Therapy and Slow Deep Breathing have been shown to reduce both systolic and diastolic blood pressure in hypertensive clients. Further study using the control group as a comparison is recommended